BIOM-38. PI3K/AKT/mTOR SIGNALING PATHWAY ACTIVITY IN IDH-MUTANT DIFFUSE GLIOMA. (9th November 2020) - Mohamed, Esraa; Kumar, Anupam; Hilz, Stephanie; Wang, Albert; Shai, Anny; Taylor, Jennie; Clarke, Jennifer; Molinaro, Annette; Lee, Julieann; Costello, Joseph; Solomon, David; Phillips, Joanna
Abstract: PI3K/AKT/mTOR signaling pathway activation is a common mechanism of tumor progression in diffuse lower grade glioma. Robust and accurate biomarkers are needed to stratify patients for therapies targeting this pathway. To investigate the potential of phosphoprotein quantification to provide a direct and functional pathway readout, we analyzed 90 tumors from 83 patients with IDH-mutant diffuse glioma. The cohort comprised 50 IDH-mutant astrocytomas, 40 IDH-mutant and 1p/19q-codeleted oligodendrogliomas, 7 of whom had paired samples from initial diagnosis and recurrence. We developed and validated a pipeline using multiplex immunofluorescence to quantify tumor cell-specific phospho-protein expression of 3 pathway nodes, ribosomal protein S6 (RPS6), PRAS40, and 4E-BP1. In oligodendroglioma the fraction of tumor cells expressing each of the three phosphorylated proteins increased with tumor grade (p< 0.05). Comparing tumors at initial diagnosis (n=48) and at recurrence (n=42), p-RPS6 and p-PRAS40 increased in tumor cells (p< 0.05) and there was an overall increase in intertumoral heterogeneity of signaling activity at recurrence (p< 0.04). Analysis of paired samples demonstrated increased signaling pathway activity in a subset at recurrence. Robust signaling activity, defined as a phospho-positive tumor cell fraction ≥ median for all three phosphoproteins, was identified in 71.4% of grade 3 IDH-mutant astrocytoma(5/7) and 45.4% of grade 3 IDH-mutant, 1p/19q-codeleted oligodendroglioma(5/11). In a subset of cases analyzed by targeted NGS, robust signaling pathway activity was identified in 38%(11/29) at the protein level while genetic alterations predicted to activate the pathway were present in only 17.2% (5/29). Our results demonstrate robust PI3K/AKT/mTOR signaling activity in a significant fraction of IDH-mutant diffuse glioma, an association with increasing tumor grade in oligodendroglioma, and an increase at recurrence in both oligodendroglioma and astrocytoma. Overall, our data suggest that quantitative evaluation of phosphoproteins may be a sensitive method to detect PI3K/AKT/mTOR pathway activity and may be useful for patient stratification.